Curling for Cash: The “Professionalization” of a Popular Canadian Sport - Apostle, Richard (Culture, 1992)
This essay considere the sport of curling as practiced in Canada. At a general level, I propose that the cultural understandings which have grown around the sport are important for an assessment of its social importance. In particular, I intend to examine some of the conflicting meanings which participants have created through their involvement in the sport. I will point to the ways in which the sport is implicated in the construction and renegotiation of basic value orientations, and the ways in which curlere, especially competitive ones, test social boundaries through sophisticated forms of cheating.